A crise juvenil ante o sagrado institucional e a busca de uma espiritualidade na mística de Paula Frassinetti - Araújo, Wandekarla Bônia de (2008)
This dissertation attempts to be a deep look at the particular universe of the adolescents from secondary schools and young university students, catching a glimpse in a dialogue and systematic approach with themselves and the church, and the church with the adolescents and juvenile people disenchanted with the institutional sacred and, therefore, living a religious crisis. Our proposal is, above all, to provide a broad knowledge of the factors which unleashing factors of this crisis in the presence of the sacred and the identification of clues to one new juvenile spirituality, in the mystic of Paula Frassinetti. The studies about adolescence and the youth in general, report and characterize this crossing to the maturity as something very important in the formation of the adolescent and juvenile psycho-religious identities mainly when we treat of the juvenile crisis in the presence of the institutional sacred. The partial results, acquired along the work with adolescents (São José School, CECOSNE) and the university students (FAFIRE) and through the field investigation, are attempts of an approach with this public, making them aware of psycho-religious and spiritual experiences present in this phase of life. The research showed, on one hand, a confusing youth in some points related to the spirituality and religious presence. On the other hand, we could observe a unique spiritual experience in the way the young people think; this experience lived by wishes, affection, happiness, sympathy, and the avoidance of everything which was dogma, rules and acts without no sense in their lives in constant change. The crossing of an adolescent spirituality and juvenile heterogeneous to one more autonomous is well-characterized in the field search, but we can notice that the adolescent crisis is more vivid than the juvenile in the presence of the institutional sacred without having, nevertheless, the essential loss of juvenile spirituality which is more centered in front of the Other (God) than the religious institution. At last, with this study, we intend to contribute methodologically with techniques and resources which could be used to re-enchant the sacred to the juvenile universe, providing the protagonist of a new spirituality according Saint Paula Frassinetti